IMPLEMENTASI KEBIJAKAN PELESTARIAN SENI TRADISIONAL (Studi Kasus di Dinas Kebudayaan dan Pariwisata Kota Bandung) - Dian Susanti (Jurnal Sosial Politik Unla, 2019)
The background of the problem of this research is that the implementation of traditional art preservation policies in the Bandung City Culture and Tourism Office is not yet optimal. From the background of the problem the researcher identifies the problem as follows: How to implement traditional art preservation policies in the Bandung City Culture and Tourism Office. What are the factors supporters and inhibitors of the implementation of traditional art preservation policies in the Bandung City Culture and Tourism Office and what efforts have been made by the Bandung City Culture and Tourism Office in implementing policies on preserving traditional arts in the City of Bandung. The foundation of this theory uses the Policy Implementation theory, the researchers formulated the proposition as follows: "Implementation of the Policy of Preservation of Traditional Arts in the City of Bandung" will be optimal if you pay attention to the dimensions of Communication, Resources, Disposition and Bureaucratic Structure. The method in this research is qualitative and the type of research used is descriptive approach. Sources of data obtained through participant observation, in-depth interviews, literature study and documentation. Sources of data used in this study are primary data, secondary data. Data analysis techniques used in this study are data analysis in the field of Miles and Huberman models, namely data collection, data presentation, data reduction and drawing conclusions. The results of this study are that the implementation of traditional art preservation is based on Bandung City Regulation Number 5 of 2012 concerning Preservation of Traditional Art. In the implementation of the policy, the factors that hamper the implementation of the preservation of traditional arts and the efforts made by the Office of Culture and Tourism in implementing policies to preserve traditional arts in the city of Bandung are the lack of socialization and communication of rules and policies to art groups in Bandung and the lack of response to art groups in the city of Bandung, the lack of facilities and infrastructure to support traditional arts from the Bandung City Culture and Tourism Office.